Fairy dust and the quest for the egg - Levine, Gail Carson. frey50; Christiana, David (New York : Disney Press, 2005)
After a hurricane injures the fairies' godlike Mother Dove, whose magical feathers and precious egg are of powerful importance to both fairies and Neverland itself, it falls to newcomer Prilla and two companions to set things right.
Keywords: Fairies; Never-Never Land (Imaginary place); Fairies; Never-Never Land (Imaginary place); Fairies; Never-Never Land (Imaginary place); Fiction; Juvenile works